2019
DOI: 10.3389/fpsyt.2019.00710
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection and Outcome in Borderline Personality Disorder

Abstract: Borderline personality disorder (BPD) is a severe and heterogeneous mental disorder that is known to have the onset in young age, often in adolescence. For this reason, it is of fundamental importance to identify clinical conditions of childhood and adolescence that present a high risk to evolve in BPD. Investigations indicate that early borderline pathology (before 19 years) predict long-term deficits in functioning, and a higher percentage of these patients continue to present some BPD symptoms up to 20 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 106 publications
4
43
0
5
Order By: Relevance
“…In a recent study [7], we found that for young people referred to child and adolescent mental health services who completed the UEQ at initial screening (85%), only one third of males compared to two thirds of females reported distressing PLEs, which highlights potential sex variation in referral patterns and research/treatment access for young people reporting PLEs. However, the fact that we did not find associations between cognitive-developmental markers and severity of distressing PLEs in this sample possibly indicates a later mood and emotional dysregulation model of distressing PLEs in females, which is consistent with previous research [8,46]. This means that associations of distressing PLEs with specific aspects of cognitive and developmental functioning may become less pronounced with age and vary according to sex, with other emotional, cognitive and behavioural processes becoming more pertinent in distress maintenance over time.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study [7], we found that for young people referred to child and adolescent mental health services who completed the UEQ at initial screening (85%), only one third of males compared to two thirds of females reported distressing PLEs, which highlights potential sex variation in referral patterns and research/treatment access for young people reporting PLEs. However, the fact that we did not find associations between cognitive-developmental markers and severity of distressing PLEs in this sample possibly indicates a later mood and emotional dysregulation model of distressing PLEs in females, which is consistent with previous research [8,46]. This means that associations of distressing PLEs with specific aspects of cognitive and developmental functioning may become less pronounced with age and vary according to sex, with other emotional, cognitive and behavioural processes becoming more pertinent in distress maintenance over time.…”
Section: Discussionsupporting
confidence: 92%
“…7 However, health professionals can show reluctance to diagnose young people with BPD. 10 This reluctance has potential to not only limit the types of services individuals can access, but also delay access to effective treatment, 8,10 and it may increase the risk of suicide for this population. 11,12 It is recommended that GPs screen for BPD and refer young people to adolescent psychiatric services for further assessment if BPD traits are present.…”
Section: Identify Emerging Personality Disordermentioning
confidence: 99%
“…Besonders problematisch ist die berufliche Integration (Zanarini et al 2010;Kramer et al 2017;Álvarez-Tomás et al 2018). Für die Entwicklung der psychosozialen Funktionseinschränkungen ist offensichtlich nicht nur die Störung selbst, sondern auch die prämorbide Entwicklung beteiligt, etwa durch Ausbildung maladaptiver Schemata, Folgen komplexer Traumatisierung und ungünstiger psychosozialer Entwicklungsbedingungen (Bozzatello et al 2019).…”
Section: Einführungunclassified